Cut and Conceptlism in Matías Celedon S la Filial 2013 [Corte y Conceptualismo en la Filial 2013 de Matías Celedón] - Reyes-Gil, S (Department of Spanish Literature of the University of Granada, 2020)
Matías Celedón s “novel” La Filial (2013) is an hybrid text in its materiality and conceptual writing strategies. This article highlights literary genealogies of Celedón s work, related to visual poetry and some forms of conceptualism in literature. The text is analyzed through the notion of "cut", investigating how the text is written from disruptions in time and space, where states of exception can be associated, as well as forms of alienation and estrangement. The heterogeneity of codes and registers, the minimalism as an object, the ambiguous and figurative language, are some of the features in La Filial that makes this work an artifact throughout its possible to question the way in which we construct memory and history. © 2020 Department of Spanish Literature of the University of Granada. All rights reserved.